Steric-hindrance effect and self-sacrificing template behavior induced PDA@SnO2-QDs/N-doped carbon hollow nanospheres: Enhanced structural stability and reaction kinetics for long-cyclic Li-ion half/full batteries - Song, Huihui; Tian, Kun; Fang, Zhengyuan; Guan, Chaohui; Jiang, Huiying; Lu, Mi; Zhang, Minshu; Zhuang, Shuxin; Wei, Hao; Wei, Dong; Li, Xiaodan (Journal of colloid and interface science, 2023)
A SnO2-QDs/PDA hollow nanosphere assembled by ultrafine SnO2 quantum dots (SnO2-QDs) and nitrogen-doped carbon, containing residual polydopamine (PDA) core was prepared by PDA-assisted hydrothermal methods. PDA polymer acted as a steric hindrance and sacrificed template during the hydrothermal reaction of metal salts to achieve the formation of ultra-small metal oxide particles and hollow spheres. The strong interaction between the ultra-small SnO2-QDs and N-doping carbon layer in the hollow structure could effectively accommodate the volume expansion and maintain structural stability. Furthermore, the residual PDA core inside the hollow sphere further captures the oxygen free radicals in the rechargeable batteries and influences the composition of the SEI layer and interface dynamics which enhances the reversibility of the conversion reaction. This synergistic strategy makes SnO2-QDs/PDA hollow nanosphere obtain a high reversible capacity (∼1200 mAh g−1) and long cycle stability (>3000 cycles). Thus, the SnO2-QDs/PDA||LiFePO4 full cell at 0.3 A g−1 exhibits excellent cycle stability with a good retention rate after 200 cycles. This study provides a new basis for the improvement of the lithium storage performance of metal oxide anode. [Display omitted] •Steric-hindrance effect and self-sacrificing template behavior induced PDA@SnO2-QDs/NC hollow nanospheres is designed.•The role of PDA core in the formation of the SEI layer on PDA@SnO2-QDs/NC hollow nanospheres is discussed.•Strong interaction between SnO2-QDs and the carbon outerwear derived from PDA accommodate the bulk expansion of electrode.•Li-ion half/full cells show superior rate performance and durable cyclic stability. Tin-based anode materials with high theoretical specific capacity are subject to huge volume expansion and poor reaction reversibility, leading to degradation of battery performance. Herein, the steric-hindrance effect and self-sacrificing template behavior of polydopamine were firstly developed to induce the formation of hollow nanospheres assembled by ultrafine SnO2 quantum dots (SnO2-QDs) and nitrogen-doped carbon (NC), containing residual polydopamine (PDA) cores. The PDA@SnO2-QDs/NC hollow nanospheres could effectively accommodate the volume expansion and maintain structural stability. More importantly, the PDA core could capture oxygen free radicals produced by the charge/discharge process and be involved in the evolution of the SEI layer, achieving enhanced electrochemical reaction kinetics. The optimized PDA@SnO2-QDs/NC anode shows a specific capacity of 898 mAh g−1 after 300 cycles at 0.3 A g−1, and scarcely capacity attenuation after 1500 cycles at 1 A g−1. The long-cyclic life is up to 3000 cycles at 3 A g−1. Even after 200 cycles, the anode in the PDA@SnO2-QDs/NC||LFP full battery gives a reversible capacity of 489 mAh g−1 at 0.3 A g−1, with a capacity retention of 77 %. This work casts new light on tin-based anode materials and interface optimization.